2020
DOI: 10.1080/14693062.2020.1754157
|View full text |Cite
|
Sign up to set email alerts
|

The Brazilian renewable energy policy framework: instrument design and coherence

Abstract: In the context of Brazil's rising energy-related greenhouse gas (GHG) emissions, we develop a forwardlooking analysis of the domestic renewable energy policy framework. We probe the overall effectiveness of this framework by focusing on instrument design (in terms of stringency and predictability) as well as policy coherence. We analyze the development of solar, wind and hydropower, as well as biodiesel and ethanol, in the period between 2003 and 2018. We find strong increases in stringency for biodiesel, sola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 24 publications
1
6
0
3
Order By: Relevance
“…In the field of renewable energy policy, Mamat et al ( 2019 ) found that the barriers of renewable energy policy implementation were social, political and economic pressures in Southeast Asia. The similar studies can also be seen in Gungah et al ( 2019 ) and Fraundorfer and Rabitz ( 2020 ). As for the renewable energy supply chain, studies like Fernando et al ( 2018 ) showed that renewable energy supply chain management enables companies to achieve competitiveness in Malaysia.…”
Section: Introductionsupporting
confidence: 85%
“…In the field of renewable energy policy, Mamat et al ( 2019 ) found that the barriers of renewable energy policy implementation were social, political and economic pressures in Southeast Asia. The similar studies can also be seen in Gungah et al ( 2019 ) and Fraundorfer and Rabitz ( 2020 ). As for the renewable energy supply chain, studies like Fernando et al ( 2018 ) showed that renewable energy supply chain management enables companies to achieve competitiveness in Malaysia.…”
Section: Introductionsupporting
confidence: 85%
“…Os leilões de energia renovável no Brasil ocorrem através de leilões regulares ou de leilões de reserva, estes últimos, desde 2009, orientados a licitar fontes não convencionais de energia, especialmente eólica (AQUILA et al, 2017). Cobrindo quase três quartos do mercado doméstico de eletricidade, o sistema de leilões se tornou o principal instrumento de política, permitindo expandir e diversificar a oferta de energia renovável (FRAUNDORFER & RABITZ, 2020).…”
Section: Políticas Públicas Em Energias Renováveisunclassified
“…Entretanto, as novas capacidades são licitadas com base nas previsões de demanda das empresas de distribuição no curto prazo, gerando flutuação substancial dos volumes e o cancelamento frequente de leilões programados, de tal forma que a previsibilidade é baixa (FRAUNDORFER & RABITZ, 2020). No total, entre 2009 e 2021, contratos foram concedidos para 19,5 GW de capacidade de energia eólica e 5,2 GW para solar fotovoltaica, entretanto, existiu uma significante variação ano a ano (ANEEL, 2021).…”
Section: Políticas Públicas Em Energias Renováveisunclassified
“…As observed by Pergher (2011), in the search for renewable sources, Brazil presents a significant differential concerning other countries because its biodiversity allows the generation of energy through various means, including hydroelectric, solar, and wind, besides the development of alternative sources such as the use of biomass, used for the production of renewable fuels, such as ethanol, biodiesel, among others (Agronegócios and Tecnologias, 2006;Fraundorfer and Rabitz, 2020). According to the Balanço Energético Nacional do Ministério de Minas e Energia (MME), Brazil emerges as a leader in renewable energy.…”
Section: Introductionmentioning
confidence: 99%